Phenolic characterisation of red wines from different grape varieties cultivated in Mendoza province (Argentina) - Fanzone, Martín Leandro (2012)
Background: Knowledge of the chemical composition of wine and its association with the grape variety/cultivar is of paramount importance in oenology and a necessary tool for marketing. Phenolic compounds are very important quality parameters of wines because of their impact on colour, taste and health properties. The aim of the present work was to study and describe the non‐flavonoid and flavonoid composition of wines from the principal red grape varieties cultivated in Mendoza (Argentina). Results: Sixty phenolic compounds, including phenolic acids/derivatives, stilbenes, anthocyanins, flavanols, flavonols and dihydroflavonols, were identified and quantified using high‐performance liquid chromatography with diode array detection coupled with electrospray ionisation mass spectrometry (HPLC‐DAD/ESI‐MS). Marked quantitative differences could be seen in the phenolic profile among varieties, especially in stilbenes, acylated anthocyanins and other flavonoids. Conclusion: The polyphenolic content of Malbec wines was higher compared with the other red varieties. Dihydroflavonols represent a significant finding from the chemotaxonomic point of view, especially for Malbec variety. This is the first report on the individual phenolic composition of red wines from Mendoza (Argentina) and suggests that anthocyanins, flavanols and phenolic acids exert a great influence on cultivar‐based differentiation